Efforts to Increase through Numeracy Contextual Learning Model in Class III SD - Pebria Dheni Purnasari; Yosua Damas Sadewo (STKIP Singkawang, 2018)
This research is to improve the numeracy skills through contextual learning model in the third-grade students of SDN 10 Melakos. This research is a classroom action research (CAR) conducted jointly with third-grade teachers at SDN 10 Melakos, the subject of this study is all third-grade students of SDN 10 Melakos totalling 19 students. The data collection techniques are carried out by engineering tests and observation. The results showed that the initial conditions of students who completed their study of 38.84%, and then after being given treatment by applying the model of contextual learning in students who complete the first cycle increased to 68.42%, still well below the thoroughness of performance indicators and after repair on students who complete the second cycle into 89.47%. Their mastery learning students showed that efforts to improve numeracy skills through contextual learning model in the third-grade students of SDN 10 Melakos successfully applied.